Virtual Reality Hypermarket (VR Hypermarket) / Yin Pei Yee - Yin, Pei Yen (2006)
Virtual Reality Hypermarket is an idea to generate a virtual reality version of a hypermarket, complete with shelves, products, product database record, searching function and the show way function. Virtual Reality Hypermarket is an online operation and navigation in the three dimensional malls and stores. Besides that, it provides the searching, add, delete and edit the database record or the hypermarket stock. In the main page, the client can decide whether want to go to VR shopping or go for the main page of the website. For the VR shopping , the clients are touring in the VR environment where design was full with shelves, product in the proper placement and cashier. From here, the client was able to view the database record of product detail and product amount in the VR environment. Beside that, the client able to change the view point to the desired view point of each deparment. For home page section, there got show way function to let the customer just know the way t go for selected department they desired. Here got two functions in show way which is VR and flash. Other than, another searching function which can had searching of the product availability and showing the product detail. Another function is the administrator back office. Here the admin need to login to had additional function working like add, remove and delete the stock of database record. This system was connected with the database of storing in hypermarket to make sure the information of storing on the database is always updated and implementing through online access to the database.